Performance evaluation of self-propelled puddler for rice (Oryza sativa L. ) crop - Khadatkar, Abhijit (ORYZA-An International Journal of Rice, 2018)
Rice is an important food crop which is grown in about 43.6 million ha in India. Out of 10 major rice producing states, West Bengal is in the first place followed by Uttar Pradesh and Andhra Pradesh. Rice is grown by transplanting young rice seedlings manually in bending and squatting posture. It is well known that before transplanting a soft seedbed is prepared that requires puddling as a secondary tillage opeartion. In India, the machineries which are being used for puddling operation normally are animal drawn puddler, tractor's cagewheel and power tiller operated rotary tiller. The performance evaluation of developed puddler for rice crop was carried out in the experimental field of Agricultural and Food Engineering Department, IIT, Kharagpur inIndia. The result indicated the average value of puddling index obtained was 59.6% for the first pass (P1) and 77.5 % second pass (P2). The average depth of puddle was 10.7 cm for the developed puddler which is at parwith that of rotary tiller.